Changing the surface of the 07C11-KV mixed fabric modified by carbon and zirconium clusters, during climate tests - A. G. Anisovich; M. I. Markevich; I. P. Akula; N. M. Chekan; E. N. Shcherbakova; E. V. Kevra (Литьë и металлургия)
The technology of modification of textile mixed materials using carbon and zirconium targets has been developed. A change in the structure of a composite material based on a 07C11‑KV mixed fabric (produced by Mogotex OJSC) modified with carbon and zirconium clusters after exposure at low temperatures (up to ‑40 °C) in a climatic chamber was investigated. It is shown that at temperatures ‑20 – ‑30 °C, the material is de‑fibrous. At ‑40 °C, there is no de‑fibering, fiber straightening is observed. The continuity of the coating is maintained for all test variants.